Endophytic Fungus Phomopsis liquidambaris Enhances Fe Absorption in Peanuts by Reducing Hydrogen Peroxide - Du, Ying-Chun; Kong, Ling-Jie; Cao, Ling-Sen; Zhang, Wei; Zhu, Qiang; Ma, Chen-Yu; Sun, Kai; Dai, Chuan-Chao (Frontiers in Plant Science, 2022)
Iron (Fe) deficiency in alkaline calcium soil is a problem that needs to be solved urgently as Fe is an essential and commonly limiting nutrient for plants. Endophytic fungus, Phomopsis liquidambaris (P. liquidambaris), has been reported to promote Fe absorption in peanuts (Arachis hypogaea L.), however, the mechanisms remain unclear. Under prolonged Fe deficiency, an increase in hydrogen peroxide (H2O2) often triggers a series of signaling events and leads to the inhibition of Fe acquisition. The main purpose of this study was to explore whether and how the endophytic fungus P. liquidambaris promote Fe absorption in peanut through regulating H2O2 and assisting in resisting oxidative stress. In this study, we detected the Fe deficiency-induced transcription factor (FIT), Fe2+ transporter (IRT1), and ferric reduction oxidase 2 (FRO2) of peanuts, and confirmed that they were negatively related to Fe concentration. Similarly, FIT, IRT1, and FRO2 were also inhibited by H2O2. The addition of P. liquidambaris reduces H2O2 under Fe-deficiency with an increase in Fe content, while the exogenous addition of H2O2 further decreases it, and the addition of catalase (CAT) under Fe-deficiency reverses this phenomenon. Through transcriptome analysis, we proved that the expression of FIT, IRT1, FRO2 and CAT are consistent with our hypothesis, and P. liquidambaris has a stress-mitigating effect on peanuts mainly via CAT, glutathione peroxidase, and malondialdehyde. Our study proved the Fe-absorption promoting effect and stress mitigation effect of P. liquidambaris under Fe-deficiency in peanuts, and their combined usage may help peanuts grow better